Risk Factors for Fear of Falling in Elderly Patients with Severe Knee Osteoarthritis before and One Year after Total Knee Arthroplasty. (December 2016) - Tsonga, Theano; Michalopoulou, Maria; Kapetanakis, Stylianos; Giovannopoulou, Eirini; Malliou, Paraskevi; Godolias, George; Soucacos, Panagiotis
Purpose: To evaluate the regression of fear of falling (FOF) and identify its risk factors in patients with severe knee osteoarthritis before and one year after total knee arthroplasty (TKA). Methods: 11 men and 57 women with a mean age of 73 years and a mean body mass index of 30.36 kg/m 2 who had severe (grade 3 or 4) knee osteoarthritis and knee pain of ≥1 year were included. Two weeks before and one year after TKA, patients were asked about their FOF status and falls history. Patients were asked to complete the Physical Activity Scale for the Elderly, Short Form 36 (SF-36), and Western Ontario and McMaster Universities Arthritis Index (WOMAC) questionnaires. Clinical performance was assessed using the Berg Balance Scale and Timed Up and Go (TUG) test. Results: Of the 68 patients, 56 (82.4%) had FOF preoperatively and 30 (44.1%) had FOF one year after TKA (p<0.001). The strongest predictors for FOF preoperatively were fallers (odds ratio [OR]=9.83, p=0.028), mental component summary (MCS) score of SF-36 (OR=0.88, p=0.024), and TUG (OR=3.4, p=0.013). The strongest predictors for FOF one year postoperatively were fallers (OR=16.51, p=0.041), patients with ≥2 chronic diseases (OR=17.33, p=0.011), physical function score of WOMAC (OR=1.015, p=0.005), and MCS score of SF-36 (OR=0.86, p=0.015). Conclusion: TKA positively affected FOF and gradually reduced the FOF rate over a year period after TKA in an elderly population.